The construction of an order: structural adjustment in Costa Rica (1985-1995) - Raventós Vorst, Ciska 1955- ([editor no identificado], 1995)
Tesis (Doctor of Philosophy)--Faculty of Political and Social Science of the New School for Social Research, 1995.